(untitled) (Journal of Applied Learning and Teaching, 2020)
The novel coronavirus (COVID-19) pandemic has affected every sector across every corner of the world. The higher education sector is not immune from the pandemic and is facing significant learning and teaching challenges. The existing literature databases on COVID-19 are focused on the medical elements of the pandemic. This manuscript documents the method for the creation of the first version of the COVID-19 in Higher Education Literature Database (CHELD). Our aspiration is to provide an open access resource to support future learning and teaching scholars to gain timely access to pre-examined literature on higher education during COVID-19. This first version documents 138 manuscripts published or online-first between 1 January 2020 to 30 June 2020. Using a rigorous systematic review method, engaging in the PRISMA approach, quality assessment using the Mixed Method Appraisal Tool (MMAT) and Quality Assessment Tool for Theory and Literature (QATTL), we offer a first glance at the metadata of articles published on COVID-19 in higher education during the first six months of 2020. By providing an open access database, we see the opportunities for future research as boundless.